Towards a sustainable water future : proceedings of Oman's International Conference on Water Engineering and Management of Water Resources - Badr, Atef; Venables, Jean (ICE Publishing, 2022)
The proceedings of 'Towards a Sustainable Water Future' discusses new technology, explores innovative techniques and presents the latest research results by international researchers, academics, engineers, policymakers and government organisations in topics related to creating a sustainable water future. The conference covers a wide range of topics at the heart of water engineering and management of water resources, including treatment, resources management, distribution systems, water losses, sustainability, minimising adverse environmental impacts, energy efficiency, reclamation, recycling, reuse, modelling and design and maintenance of water systems and infrastructure.